Constraints on the global marine iron cycle from a simple inverse model. Issue 1 (9th January 2016) - Frants, Marina; Holzer, Mark; DeVries, Timothy; Matear, Richard
Abstract: A simple model of the global marine iron cycle is used to constrain the sources, sinks, and biological cycling of iron. The iron model is embedded in a data‐assimilated steady state circulation, with biological cycling driven by a prescribed, data‐constrained phosphate cycle. Biogeochemical parameters are determined by minimizing a suitably weighted quadratic mismatch with available dissolved iron (dFe) observations, including GEOTRACES transects. Because the effective iron sources and sinks overlap, current dFe observations cannot constrain sources and sinks independently. We therefore determine a family of optimal solutions for a range of the aeolian source strength σ A from 0.3 to 6.1 Gmol/yr. We find that the dFe observations constrain the maximum Fe:P uptake ratio R 0 to be proportional to σ A, with a range that spans most available measurements. Thus, with either R 0 or σ A specified, a unique solution is determined. Global inventories of total and free iron are well constrained at (7.4 ± 0.2) × 10 11 and (1.39 ± 0.05) × 10 10  mol Fe, respectively. The dFe distributions are very similar across the family of solutions, with iron limitation in the known high‐nutrient low‐chlorophyll regions. Hydrothermal source strength ranges from 0.57 to 0.73 Gmol/yr and does not vary systematically with σ A suggesting that the hydrothermal and aeolian parts of the iron cycle are largely decoupled. The hydrothermal dFe anomaly in the euphotic zone is ∼10% and concentrated in subpolar regions of iron limitation. Enhanced ligand concentrations in old waters and in hydrothermal plumes are necessary to capture key features of the dFe observations. Key Points: A simple iron model is used to constrain biogeochemical parameters objectively The aeolian source and/or maximum Fe:P uptake ratio need independent constraints The hydrothermal and aeolian components of the iron cycle are largely decoupled